PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PT. CAHAYA PENGAJARAN ABADI DI KOTA BALIKPAPAN - Solly, Yisrahya; Arrywibowo, Imam; Hadiyatno, Hadiyatno (MEDIA RISET EKONOMI [MR.EKO], 2026)
The purpose of this study was to determine the effect of the work environment, work discipline and motivation on job satisfaction of employees at PT. Cahaya Pengajaran Abadi of Balikpapan City. This type of research is quantitative. The number of samples in this study were 55 employees of PT. Cahaya Pengajaran Abadi of Balikpapan City and uses sesus which means whole. The study uses the IBM SPSS Statistics 28 application is used to test CAlassical Assumption Tests, Multiple Linear Regression Analysis, and Hypotthesis test. The results showed that partially Work Environment, Work Discipline, and Motivation had a positive and significant effect on Job Satisfaction of PT. Cahaya Pengajaran Abadi of Balikpapan City. Keywords: Work Environment, Work Discipline, Motivation.